Microsegregation and Solidification Shrinkage of Copper-Lead Base Alloys - B. Korojy; L. Ekbom; H. Fredriksson (Advances in Materials Science and Engineering)
Microsegregation and solidification shrinkage were studied on copper-lead base alloys. A series of solidification experiments was performed, using differential thermal analysis (DTA) to evaluate the solidification process. The chemical compositions of the different phases were measured via energy dispersive X-ray spectroscopy (EDS) for the Cu-Sn-Pb and the Cu-Sn-Zn-Pb systems. The results were compared with the calculated data according to Scheil's equation. The volume change during solidification was measured for the Cu-Pb and the Cu-Sn-Pb systems using a dilatometer that was developed to investigate the melting and solidification processes. A shrinkage model was used to explain the volume change during solidification. The theoretical model agreed reasonably well with the experimental results. The deviation appears to depend on the formation of lattice defects during the solidification process and consequently on the condensation of those defects at the end of the solidification process. The formation of lattice defects was supported by quenching experiments, giving a larger fraction of solid than expected from the equilibrium calculation.